Late Cretaceous to Early Eocene dinoflagellate cysts from the "12 frères" borehole, Fresco, southwestern Côte d'Ivoire: Biostratigraphy and paleobiogeographic implication. (February 2019) - Guédé, Koré Élysée; Slimani, Hamid; Jean-Paul Yao, N'goran; Chekar, Mouna; Jean-Claude Koffi, N'zi; M'Hamdi, Amel; Mouah, Raymond; Digbehi, Bruno Zeli
Abstract: The Upper Cretaceous to lower Eocene sediments from the "12 Frères" borehole in Fresco, southwestern Côte d'Ivoire are here subject of a palynological study: systematic, palynostratigraphy and paleogeography. Eight thousand eight hundred and ten palynomorphs, including 68 species of dinoflagellate cysts (dinocysts), 14 species of spores and pollen grains and Chlorophyceae were identified. The biostratigraphy based on dinocyst marker events and compared with various reference sections from the Northern Hemisphere allowed us to refine to the stage level the Maastrichtian, Paleocene and Eocene deposits of the section. The dinocyst events, recorded from the base to the top of the studied section, include the last occurrences of Odontochitina operculata, Andalusiella ivoirensis, Cerodinium granulostriatum, Dinogymnium spp., Andalusiella spp., Cerodinium diebelii, highest relative abundances of Adnatosphaeridium vittatum, Kallosphaeridium yorubaense and highest relative abundances of Apectodinum spp. According to Lentin and Williams (1980), the observed dinocyst assemblages suggest a tropical to subtropical province for the studied deposits. Highlights: A palynological study is carried out in the "12 Frères" section, Fresco, Ivory Coast. The study of the cuttings samples is based on the Last Occurrences and acmes of dinocyst taxa. The deposits are dated Early–Late Maastrichtian, Danian, Selandian–Thanetian, Ypresian. The dinocysts suggest a tropical to subtropical province for the Cretaceous deposits.